Estudio dendroclimático de las rachas secas y húmedas en el Sector Central de la Depresión del Ebro - Saz Sánchez, Miguel Ángel; Creus Novau, José (Geographicalia, 2017)
With the dendroclimatic series of precipitation in Pallaruelo de Monegros weather station (placed in the mid-eastern sector of the Ebro Basin), we study the dry and humid periods between years 1465 and 1989, analysin its frequency, duration and intensity. The characterization of the years according to its total precipitation has allowed us to see as most remarkable facts the almost total lack of sequences of normal years and the exceptional behaviour of the precipitation in XXth century.
Keywords: Dendroclimatology; Ebro valley; drought; rainfall variability